Implementation of fuzzy controller based active filter for harmonic mitigation of grid-connected PV-system - Khandelwal, Achala; Joshi, Namra (Institute of Advanced Engineering and Science, 2024)
Incorporating photovoltaic (PV) systems to grids have developed into an obvious alternative for many countries, those results in harmonics issues for the utility operators. Harmonics arises due to extensive utilization of power-electronic components during incorporation of PV to grid. Harmonic deformation has traditionally been taken care of by the relevance of passive filter. Active filters have come up as an alternative choice over passive ones for reduction of harmonic due to existence of several advantages in comparison to previous filter. The application of controllers is the most significant aspect of using an active filter. Various investigations are beneath development to progress performance of the filters. Control of capacitor voltage is among the major regulation requirement for the filter. Here, regulation of voltage is carried on by fuzzy-controller. The article represents compensation of harmonic currents of a grid integrated PV-system by application of fuzzy-controller placed active filter. One of the important control requirements of filter is the regulation of DC link up capacitor voltage. Here the voltage supervision of capacitor is being done using PI controller. The paper shows current harmonics compensation of PV grid connected system using PI controller based active filter. Simulating results are revealed that shows the harmonics are contained inside IEEE limits.